Eco-friendly and climate smart biopesticides developed and evaluated for their efficacy on target pests - Nwilene, F.; Adeoti, A.; Nacro, S.; Ouattara, D.; Umaru, A.; Oladigbolu, A. (2024)
Insect pests such as the rice stem borers (African rice gall midge (AfRGM) Orseolia oryzivora, and Diopsis spp.) are among the economically most important pests of rainfed upland/lowland and irrigated rice in Sub-Saharan Africa. The African rice gall midge, Orseolia oryzivora Harris & Gagné (Diptera: Cecidyomyiidae), is an insect pest primarily of rainfed and irrigated lowland rice, and occurs only in sub-Saharan Africa. The larvae cause severe crop damage during the vegetative stages (seedling to panicle initiation) by producing tube-like ‘silver shoot’ or ‘onion leaf’ galls that prevent panicle production. Dipterous stem borers (the stalk-eyed flies – Diopsis spp.) are the most economically important stem borer species of rainfed upland/lowland and irrigated rice in Nigeria. The larvae of stem borers cause significantly yield loss during the vegetative (seedlings to panicle initiation) and reproductive stages by producing deadhearts and whiteheads, respectively, which prevent panicle development. The extensive use of synthetic insecticides to control these pests has raised concerns regarding environmental and human health. Consequently, this has necessitated the need for alternative control measures such as biopesticides. Identifying the use of biopesticides such as botanicals and Entomopathogenic fungi are most promising options for managing AfRGM and stem borers on rice.